On modeling the compact spread of a thickening reagent in a plane-radial filtration flow - Polyakov, V.L. (Reports of the National Academy of Sciences of Ukraine, 2017)
A mathematical task of the immiscible fluid (reagent) spreading within a head reservoir is posed. Its viscosity depends on the residence time by the exponential or hyperbolic law. The exact solution is obtained to predict the plug flow displacement and injection well discharge. The specific features of the formation of three zones in a cylindrical flow field and a growth of losses of the head in time are analyzed by a number of examples.